The Impact of Impulsive and Reflective Cognitive Styles on the Problem-Solving Skills of Pre-service Elementary Teacher Students - Susiloningsih, Wahyu; Prastyo, Danang; Fanny, Arif Mahya (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study investigates the influence of individual cognitive styles, specifically impulsive versus reflective, on problem-solving performance among pre-service elementary teacher students (PGSD). Employing a quasi-experimental design with intact class grouping, 64 participants were categorized via the Matching Familiar Figures Test (MFFT) into impulsive (n equals 28) and reflective (n equals 36) cognitive-style groups. Subsequently, participants completed problem-solving tasks designed according to the four stages of the Polya model, emphasizing higher-order cognitive processes aligned with the C4 to C6 levels of Bloom’s taxonomy. Data analysis was conducted using one-way analysis of variance (ANOVA) to determine whether significant differences exist between groups. Results reveal a statistically significant difference in problem-solving performance: reflective students outperformed impulsive ones (F equals 25.789, p is less than 0.001). Reflective learners demonstrated greater accuracy, deeper reasoning, and more systematic approaches, whereas impulsive learners tended to respond faster but with increased error rates and less elaboration. The observed effect size suggests that cognitive style accounts for a substantial portion of variance in problem-solving outcomes, underscoring its pedagogical relevance. These findings have significant implications for teacher education and classroom practice. Recognizing differences in cognitive styles can help instructors design differentiated instructional strategies that cater to diverse learning needs. Future research could further explore the long-term effects of cognitive-style-aware instruction and examine contextual moderators, such as subject matter or learning environment, that may influence its effectiveness.